2022
DOI: 10.1073/pnas.2214911119
|View full text |Cite
|
Sign up to set email alerts
|

PLK1-ELAVL1/HuR-miR-122 signaling facilitates hepatitis C virus proliferation

Abstract: The liver-specific microRNA, miR-122, plays an essential role in the propagation of hepatitis C virus (HCV) by binding directly to the 5′-end of its genomic RNA. Despite its significance for HCV proliferation, the host factors responsible for regulating miR-122 remain largely unknown. In this study, we identified the cellular RNA-binding protein, ELAVL1/HuR (embryonic lethal-abnormal vision-like 1/human antigen R), as critically contributing to miR-122 biogenesis by strong binding to the 3′-end of miR-122. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
(54 reference statements)
0
15
0
Order By: Relevance
“…In summary, although there is still a tendency to use rigosertib as a Plk1 inhibitor [16,[25][26][27], the Plk1 inhibition mechanism for rigosertib is controversial, as there is strong evidence that this may not be the real mechanism and some alternative mechanisms have been described for the mitotic arrest phenotype.…”
Section: Rigosertib As a Plk1 Inhibitormentioning
confidence: 99%
“…In summary, although there is still a tendency to use rigosertib as a Plk1 inhibitor [16,[25][26][27], the Plk1 inhibition mechanism for rigosertib is controversial, as there is strong evidence that this may not be the real mechanism and some alternative mechanisms have been described for the mitotic arrest phenotype.…”
Section: Rigosertib As a Plk1 Inhibitormentioning
confidence: 99%
“…In PNAS, Seo et al. ( 11 ) reported that a protein–miR-122 complex is modulated by a signaling cascade to enhance HCV gene amplification. This finding is very exciting because it opens the possibility to target upstream signaling factors of miR-122 than directly miR-122.…”
mentioning
confidence: 99%
“…( 13 ) observed effects of ELAVL1/HuR depletion on replication and Seo et al. ( 11 ) noted effects on translation of the viral RNA. Of course, effects of ELAVL/HuR-miR-122 depletion on translation may be a consequence of stabilization of the viral RNA by this protein–miR complex against the attack of 5′ RNA triphosphatase DUSP11 ( 15 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations